Kinetics and Thermodynamics of (1+2) Cycloadditions of Transient Diphenylgermylene with Alkenes - SAEIDI, HAYENIAZ YASER (My University, 2012)
1,1-Dimethyl-3-phenyl-1-germacyclopent-3-ene (32) was synthesized and it was used for the study of the reactivity of diphenylgermylene (GePh2) toward alkenes using steady state and nanosecond laser flash photolysis technique (nLFP) in hexanes solution.
The reactivity of GePh2 toward several alkenes including 1-hexene, cis-2-hexene, trans- 3-hexene, cyclopentene, cyclohexene, cis-cyclooctene, methylcyclohexene, 2-methyl-2- pentene, 2-methyl-1-pentene and trans-3-methyl-2-pentene has been investigated by nLFP method. In all cases, the equilibrium constant was measured and it was found that there is a direct correlation between the Gibbs free energy of the reaction (∆Gr) and the ionization potential (IP) of the involved alkene. This indicates that alkenes with higher IP, electron poor alkenes, should lead to more stable germiranes and consequently installation of electron withdrawing groups on alkenes should stabilize the resulting germirane. This is the first time such a quantitative predictor is reported.
Steady state photolysis methods have been used to investigate same aspects of germirane reactivity. Photolysis of 32 in the presence of acrylonitrile and methanol in one experiment, and 3,3-dimethyl-1-pentene and methanol in another experiment, has provided more evidence for the presence of the corresponding germiranes which were trapped by methanol.
Finally, the (1+2) cycloaddition reactions of GeH2, GeMe2 and GePh2 with a selection of alkenes were investigated computationally using different DFT methods and 6-311+G(d,p) as the basis set. The results show that the reaction becomes less exergonic moving from GeH2 to GeMe2 and then to GePh2. In addition, plots of calculated ∆Gr against the experimental IP of the involved alkene reproduced the observed experimental correlation from the laser studies. It was also concluded that ωB97XD and mPW1PW91 are the most reliable of the DFT methods that were investigated.
Keywords: germylene; germirane; photochemistry; transient; thermodynamics; kinetics; (1+2) cycloaddition; stability; Inorganic Chemistry; Organic Chemistry; Physical Chemistry; Inorganic Chemistry